Game meaning in Kant’s aesthetic theory as the paradigm of European artistic thinking (Proceedings of Southern Federal University. Philology, 2015)
Strelnikova Larisa YurievnaThe article proves that Kant includes in his philosophy the concept of the game as an aesthetic principle. The game is identified with art as a free activity, which has no practical purpose and delivers the pleasure of beauty. Kant opens in creative game dual nature - a combination of reason and imagination, reflecting the duality of his philosophic system and giving rise to the idea double world in Romanticism and fragmented consciousness in contemporary literature. In modern works the writer assumes the functions of Magister Ludi, creating its own gaming procedure of the artistic space.Key words: imagination and reason, dualism, Kant’s aesthetics, knowmen, free game, double world.